2024
DOI: 10.1037/rel0000493
|View full text |Cite
|
Sign up to set email alerts
|

In the wake of religious conversions: Differences in cognition and emotion across three religious communities of an indigenous tribe in Malaysia.

Abstract: The Indigenous spirituality of a hunter-gatherer tribe (Temiar) of Peninsular Malaysia, in the Southeast Asian region, has been fractured by religious conversions into three religious communities-Traditional, Muslim, and Christian. Based on the theoretical framework of strong-ties and weak-ties rationalities (Sundararajan, 2020), this study explored the varying degrees of change in cognition and emotion when the kinship-based spirituality of Indigenous Temiar came under the influence, through conversion, of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Over the past two decades, some Temiar have converted to Christianity, and this has resulted in the Christian Temiar having a more independent form of self-construal and, importantly, an associated change in cognitive style from more concrete/presentoriented to more abstract/future-oriented. As Thong et al (2023) concludes:…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Over the past two decades, some Temiar have converted to Christianity, and this has resulted in the Christian Temiar having a more independent form of self-construal and, importantly, an associated change in cognitive style from more concrete/presentoriented to more abstract/future-oriented. As Thong et al (2023) concludes:…”
mentioning
confidence: 90%
“…How the self is construed has a strong influence on various cognitive processes, including how attention is oriented and how emotions are experienced (Markus & Kitayama, 1991;Lillard, 1998;Luhrmann et al, 2011), and even a person's level of trait mindfulness (Jankowski et al, 2022). Research has also shown that a person's selfconstrual can change: for example, when moving to a new culture (Berry et al, 2006;Sam & Berry, 2010;Chen et al, 2015), as a result of religious conversion (Thong et al, 2023;Winchester, 2015;Snook et al, 2019;Luhrmann et al, 2011;Robbins, 2004), or even as a community adopts modern technology (Hansen et al, 2012). Given that different forms of self-construal are associated with differences in how an individual processes information and are also cultivated by, and adaptive in, different environments, the construal of the self has also been referred to as a type of cognitive style (Yu, 2021).…”
Section: Cultural Influences On Self-construalmentioning
confidence: 99%
See 1 more Smart Citation
“…In the remainder of this essay, I present a tapestry of Indigenous accounts of ecological grief based on two strands of ethnography. One strand comes from Hernandez’s (2022) studies of Indigenous peoples in Latin America; the other strand consists of excerpts from interviews (Thong et al, 2023) with a hunter gatherer tribe of the Orang Asli in Malaysia. With a population estimate of 146,412, the Orang Asli are the earliest dwellers of Peninsular Malaysia.…”
Section: Ecological Griefmentioning
confidence: 99%
“…Values such as collectivism are privileged among strong-ties dominant societies, while individualism is privileged among weak-ties dominant societies (Sundararajan & Yeh, 2021). Research has also identified some associations between certain religions or ethnicities that historically embody kinship and bloodline as important and their members being more dominant in strong-ties rationality (Thong et al, 2022;Ting & Zhang, 2021;Yeh et al, 2022).…”
Section: Cultural Domains and Public Stigmamentioning
confidence: 99%